Antimicrobial mechanisms and secondary metabolite profiles of Streptomyces hygroscopicus subsp. hygroscopicus 5–4 against banana fusarium wilt disease using metabolomics - Yun, Tianyan; Jing, Tao; Zang, Xiaoping; Zhou, Dengbo; Li, Kai; Zhao, Yankun; Wang, Wei; Xie, Jianghui (Frontiers in Microbiology, 2023)
Fusarium wilt of banana (FWB) is seriously affecting the sustainable development of the banana industry, and caused by a devastating soil-borne fungus Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4). The most efficient way to control FWB is using antagonistic microbes. We previously identified Streptomyces hygroscopicus subsp. hygroscopicus 5-4 with a strong antifungal activity against the FWB. The most possible antimicrobial mechanism of strain 5-4 was explored by metabolomics approach, light microscopy imaging, and transmission electron microscopy (TEM). The membrane integrity and ultrastructure of Foc TR4 were damaged after extracts treatment, which were supported by the degradation of mycelium, soluble protein content, extracellular reducing sugar content, NADH oxidase activity, malondialdehyde content, mitochondrial membrane potential and mitochondrial respiratory chain complex enzyme activity. The extracts of strain 5-4 cultivated in different times were characterized by liquid chromatograph mass spectrometer (LC-MS). While 647 known metabolites were detected in the extracts. Hygromycin B, gluten exorphin B4, torvoside G, (z)-8-tetradecenal, piperitoside, sarmentosin, pubescenol, etc. were the main differential metabolites on fermentation culture for 7 days. Compared with strain 5-4 extracts, hygromycin B obviously inhibited mycelial growth of Foc TR4, had similar inhibitory effects on the mycelial of Foc TR4, and the EC50 concentration was 7.4 mg/L. These results showed that strain 5-4 could destroy the cell membrane of Foc RT4 by producing metabolites as hygromycin B, to inhibiting mycelial growth of Foc TR4. Streptomyces hygroscopicus subsp. hygroscopicus 5-4 might be a promising candidate strain to control the FWB, and provide a scientific basis for the practical application of hygromycin B as a biological control agent.